The Effectiveness of the TPACK-Based Problem Based Learning Model on the Learning Outcomes - Yuliani, Sri; Saputri, Kurnia (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
This study aims to determine the disparity in learning outcomes between students instructed through the TPACK-based Problem-Based Learning model in Class X at SMA Negeri 13 Palembang, as well as to examine the teaching and learning processes employed by the educators. The used research methodology is quantitative research. The research sample included class X1 with 35 students as the experimental group and class X2 with 35 students as the control group. Data collecting methods using tools include assessments and interviews. The data were analyzed with an independent samples t-test in SPSS 26. The findings indicated that the t-obtained (sig. 2-tailed) was 0.002 lower than the t-table value of 0.05, leading to the conclusion that a disparity exists in student learning outcomes between those instructed using the TPACK-based PBL model and those taught via traditional methods. The PBL methodology is beneficial for students in grade X at SMA Negeri 13 Palembang. Moreover, the interview results indicated that teachers exclusively employ a conventional instructional model, characterized by mere explanations and textbook exercises. Additionally, challenges encountered in the classroom learning process include insufficient school facilities, particularly the lack of internet connectivity, hindering access to available information, as well as the teachers' limited proficiency in utilizing existing technology.